Loan portfolio management and bank efficiency: A comparative analysis of public, old private, and new private sector banks in India - Santhosh Kumar Venugopal (Economies, 2024)
This comparative study analyzed the impact of loan portfolio composition on the efficiency of different types of banks in India-public sector, old private, and new private banks-in the period between 2013 and 2022. Efficiency was evaluated using data envelopment analysis (DEA). The study considered four loan variables-term lending, working capital, priority sector lending, and secured lending in proportion to the overall loans-as independent factors against the efficiency score as the dependent variable, using a random-effects generalized least squares (GLS) regression framework. The results indicate that there were no significant effects on the efficiency of old private banks, except for working capital, which had a marginally negative impact on bank efficiency. Working capital, priority sector lending, and term lending have been found to significantly impact the efficiency of new private banks. Only term and working capital loans significantly affected the efficiency of public sector banks.
Keywords: G21; G28; 330; banking; data envelopment analysis; efficiency; GLS regression; Hausman; priority sector